Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/children9030420
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy, Optimism, and Academic Performance as Psychoeducational Variables: Mediation Approach in Students

Abstract: Background: During the various stages of education, adolescents undergo emotional and motivational experiences that can play key roles in their development. This study aims to analyse the relationship among academic self-efficacy, optimism, and academic performance. Methods: This study comprised 1852 adolescent (male, N = 956, 51.61% and female, N = 896, 48.38%) aged 12–19 years (M = 14.77; SD = 1.80) from twelve secondary schools in Spain. The instruments used for the evaluation were the Academic Self-Efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Both emotional intelligence and optimism are positive psychology constructs related to a variety of beneficial outcomes (Brackett et al, 2011; Macleod & Conway, 2005; Malouff & Schutte, 2017; Nes & Segerstrom, 2006; Siegling et al, 2015; Usán et al, 2022). The positive and significant association between the two constructs found across studies, suggests the possibility of a mutual relationship between emotional intelligence and optimism that involves each strengthening the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both emotional intelligence and optimism are positive psychology constructs related to a variety of beneficial outcomes (Brackett et al, 2011; Macleod & Conway, 2005; Malouff & Schutte, 2017; Nes & Segerstrom, 2006; Siegling et al, 2015; Usán et al, 2022). The positive and significant association between the two constructs found across studies, suggests the possibility of a mutual relationship between emotional intelligence and optimism that involves each strengthening the other.…”
Section: Discussionmentioning
confidence: 99%
“…Emotional intelligence, as conceptualised by Mayer et al (2008), is the ability to perceive, understand and manage one's own emotions and those of others. Optimism is associated with concepts related to emotional processes such as, greater self-efficacy (Usán et al, 2022), better preventative coping skills (Nes & Segerstrom, 2006) and broader social networks (Macleod & Conway, 2005). Mayer et al (2008) proposed that emotional intelligence is an ability that is best assessed by performance measures, similar to those assessing cognitive intelligence.…”
mentioning
confidence: 99%
“…Notably, we found that adolescents with light study burden had a high frequency of tobacco consumption. Lighter self-reported study burden did not indicate better academic performance, which may be due to the low academic focus among these adolescents [ 70 ]. The present study found that adolescents with 1–2 close friends were most likely to smoke and drink, consistent with previous studies [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in the World Health Organisation’s (World Health Organization, 2014 , para.1) statement noting that adolescents “develop knowledge and skills, learn to manage emotions and relationships, and acquire attributes and abilities that will be important for enjoying the adolescent years and assuming adult roles”. Beyond functional benefits, the experiential aspect of competence (e.g., feeling effective and capable) can have positive implications for factors associated with wellbeing including optimism, self-esteem and self-efficacy (de la Barrera et al, 2019 ; Sagone et al, 2020 ; Usán et al, 2022 ).…”
Section: Competence Social Media and Adolescencementioning
confidence: 99%